Perdagangan Rempah dan Penyebaran Islam: Analisis Peran Pedagang Muslim di Nusantara Abad Ke-16 (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the relationship between the spice trade in the 16th-century Indonesian archipelago and the peaceful, gradual, and network-based spread of Islam. During this period, the Indonesian archipelago became a strategic hub for global trade, connecting the Islamic world, India, the Middle East, and Europe. In this context, Muslim traders played a crucial role as both economic actors and cultural and religious agents. Through trade interactions, marriages, the formation of coastal communities, and the dissemination of Islamic ethical values ​​inherent in trade practices, Muslim traders successfully influenced social structures and broadened local acceptance of Islamic teachings. This study uses a historical approach, examining primary and secondary sources on trade networks, migration patterns, and political dynamics in the maritime regions of the Indonesian archipelago. The analysis shows that the spice trade served not only as a means of commodity exchange but also as a medium for cultural and religious diffusion, accelerating the growth of Islamic kingdoms in various regions. These findings confirm that Islamization in the Indonesian archipelago was an integral part of the global economic network in the 16th century.